2015
DOI: 10.1103/physrevb.92.075145
|View full text |Cite
|
Sign up to set email alerts
|

Complete description of ionization energy and electron affinity in organic solids: Determining contributions from electronic polarization, energy band dispersion, and molecular orientation

Abstract: Ionization energy and electron affinity in organic solids are understood in terms of a single molecule perturbed by solid-state effects such as polarization energy, band dispersion, and molecular orientation as primary factors. However, no work has been done to determine the individual contributions experimentally. In this work, the electron affinities of thin films of pentacene and perfluoropentacene with different molecular orientations are determined to a precision of 0.1 eV using low-energy inverse photoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 99 publications
11
138
0
Order By: Relevance
“…It is however expected that when intermolecular interactions play an important role, new features in the UPS spectra coming from extended delocalization due to, e.g., hybridization of π‐orbitals or intermolecular polarization cannot be captured by the description based on the DFT calculations for a single molecule in the gas phase. Moreover, UPS spectra of the ordered molecular and polymeric systems showed a strong anisotropy and a pronounced orientation dependence with respect to the substrate or to mixing of differently terminated molecules on a molecular length scale .…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 96%
“…It is however expected that when intermolecular interactions play an important role, new features in the UPS spectra coming from extended delocalization due to, e.g., hybridization of π‐orbitals or intermolecular polarization cannot be captured by the description based on the DFT calculations for a single molecule in the gas phase. Moreover, UPS spectra of the ordered molecular and polymeric systems showed a strong anisotropy and a pronounced orientation dependence with respect to the substrate or to mixing of differently terminated molecules on a molecular length scale .…”
Section: Introduction and Formulation Of The Problemmentioning
confidence: 96%
“…In ordered thin films, large orientation dependencies of the IE were seen for molecules containing polar bonds (25). For highly ordered thin films of pentacene and perfluoropentacene, this was explained by an orientation dependence of the polarization energy originating from different charge-quadrupole interactions (26,27).…”
mentioning
confidence: 92%
“…We have demonstrated that the electron affinity of organic materials can be determined with the precision comparable to the ionization energy determined by UPS. [27][28][29][30][31][32] Using this technique, we determined the electron affinity of BCP to be 1.9 eV. 30 This value is more than 1 eV smaller than the previously assumed one suggesting that the electron transport through the LUMO level of BCP is unlikely.…”
Section: Introductionmentioning
confidence: 99%